Single-cell multi-omics dissection of c-Myb/AURKA-mediated autophagy and metabolic reprogramming in diabetic adipose-derived stem cells - Yin, Yating; Shao, Wenwen; Zha, Wen; Wang, Bin (Frontiers in Immunology, 2025)
BackgroundDiabetes mellitus (DM) alters the functional properties of adipose-derived stem cells (ADSCs), contributing to impaired tissue repair in diabetic foot ulcers (DFUs), a condition characterized by chronic inflammation. Although multi-omics studies have identified metabolic dysregulation in DM, the transcriptional and metabolic networks underlying ADSCs dysfunction remain elusive. Here, we integrated single-cell transcriptomics and metabolic profiling to characterize DM-associated ADSCs subpopulations and explored the effects of high glucose (HG)-induced inflammatory stress on autophagy, apoptosis, and metabolic reprogramming.MethodsWe analyzed single-cell RNA sequencing (scRNA-seq) data from ADSCs of three DM patients and three healthy donors. Subpopulations were clustered using Seurat, and functional annotations were performed via enrichment analysis. Autophagy, apoptosis, and metabolic pathways were assessed using AUCell scoring. Experimental validation was conducted using HG-treated ADSCs, including c-Myb/AURKA overexpression/knockdown, Co-IP, ChIP, and dual-luciferase reporter assays.ResultsWe identified fourteen ADSCs subpopulations, among which C5 (TOP2A High), C8 (AURKA High), C9 (CCNB1 High), and C11 (MMP3 High) exhibited G2/M phase preference and enhanced stemness (C11) or proliferation (C8) in DM. HG induced autophagy in ADSCs via c-Myb/AURKA pathway to resist apoptosis. Mechanistically, c-Myb directly bound to the AURKA promoter, and AURKA knockdown abolished c-Myb-induced autophagy. Metabolic reprogramming shifted toward glycolysis/gluconeogenesis in DM, particularly in C8 subpopulation.ConclusionsOur study integrates multi-omics to demonstrate that DM induces distinct ADSCs subpopulations with dysregulated cell cycle, stemness, autophagy, apoptosis and metabolic profiles. HG activates c-Myb/AURKA-mediated autophagy in ADSCs, suggesting a potential regulatory mechanism in diabetic inflammatory microenvironments. Upregulating c-Myb may restore ADSCs function in DFUs, providing a foundation for future personalized therapies.